The Relationship Between Price Stability and Financial Stability: Evidence From Major Emerging Economies. Issue 1 (2nd January 2019) - Kırcı Çevik, Nüket; Koç Yurtkur, Asuman; Dibooglu, Sel
ABSTRACT: We examine the relationship between price stability and financial stability for major emerging economies using a Markov regime-switching model. Empirical results suggest that monetary policy is consistent with the Taylor rule in all countries except for India and all countries followed both low and high inflation targeting monetary policy regimes. Low inflation targeting regime seems to be more persistent and has higher duration than high inflation targeting regimes except for Indonesia and South Africa. All countries seem to have had financial stability concerns when they formulated their monetary policy as the coefficient of the financial stress index is statistically significant at least in one regime. Overall the results suggest that Taylor rule-based monetary policies have been implemented to various degrees in major emerging economies to achieve economic stability, price stability, and financial stability.